2017
DOI: 10.1371/journal.pone.0174613
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors explain suboptimal adherence to antiretroviral therapy among HIV-infected Australian adults with viral suppression

Abstract: BackgroundMissing more than one tablet of contemporary antiretroviral therapy (ART) per month increases the risk of virological failure. Recent studies evaluating a comprehensive range of potential risk factors for suboptimal adherence are not available for high-income settings.MethodsAdults on ART with undetectable viral load (UDVL) were recruited into a national, multi-centre cohort, completing a comprehensive survey assessing demographics, socio-economic indicators, physical health, well-being, life stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…Using mobile SMS reminders to improve HIV clinical care, including keeping clinical appointments and increasing adherence to antiretroviral therapy (ART) regimens, is an emerging area (Lewis et al., ; Lunny et al., ; Schnall, Travers, Rojas, & Carballo‐Dieguez, ). ART requires life‐long adherence whereas treatment non‐adherence often have serious consequences following treatment failure leading to viral resistance, rapid disease progression and onward transmission (Siefried et al., ). In relation to ART adherence for people living with HIV, a number of studies indicate that the expected health benefits of mobile SMS, including improvement in HIV‐related biomarkers, appear promising (Finitsis, Pellowski, & Johnson, ; Garofalo et al., ; Mathes, Pieper, Antoine, & Eikermann, , ; Mbuagbaw et al., ; Rana et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Using mobile SMS reminders to improve HIV clinical care, including keeping clinical appointments and increasing adherence to antiretroviral therapy (ART) regimens, is an emerging area (Lewis et al., ; Lunny et al., ; Schnall, Travers, Rojas, & Carballo‐Dieguez, ). ART requires life‐long adherence whereas treatment non‐adherence often have serious consequences following treatment failure leading to viral resistance, rapid disease progression and onward transmission (Siefried et al., ). In relation to ART adherence for people living with HIV, a number of studies indicate that the expected health benefits of mobile SMS, including improvement in HIV‐related biomarkers, appear promising (Finitsis, Pellowski, & Johnson, ; Garofalo et al., ; Mathes, Pieper, Antoine, & Eikermann, , ; Mbuagbaw et al., ; Rana et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…There are few, if any, current, comprehensive and validated measures of patient-identified adherence barriers to ART and reasons for ART non-adherence remain inadequately understood in current resource-rich settings (Siefried et al, 2017). Hence, our research team will be developing an electronically-administered patient-reported outcome measure (PRO) to assess ART adherence barriers in the context of adult HIV care in Canada and France.…”
Section: Introductionmentioning
confidence: 99%
“…Enablers and disablers of adherence should be identified and addressed. In Australia, social/economic/cultural/patient engagement factors are associated with suboptimal adherence while ART regimen/clinical factors are not . Community‐based programmes that enhance the continuum of care could also benefit adherence and sustained viral suppression , assisting both countries in achieving the 2030 targets.…”
Section: Discussionmentioning
confidence: 99%